Assessing the Impact of Decentralization on the Quality of Indonesian Democracy - Chandra, Yenny (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
This research focuses on the impact of decentralization on Indonesian democracy, particularly post-Suharto, where decades of centralized governance shifted to a decentralized one. Drawing on Hofman & Kaiser (2006), the theoretical framework links decentralization to democracy by emphasizing political participation, regional governance empowerment, and accountability. Decentralization is not only viewed as a mechanism that provides grassroots populations with political and administrative decision-making capacities but also ensures local governments are no longer directly accountable to the central government in Jakarta and are instead responsible to their local constituents. Nevertheless, decentralization also presents challenges, and notably, in a heterogeneous society like Indonesia, the management of ethnic and religious diversity is one. While decentralization is considered the embodiment of Indonesian democracy, numerous issues have hampered efforts to improve the quality of local governance and democracy. Ultimately, decentralization and democracy are deeply interdependent, as the quality of one shall reflect on the other. Keywords: Indonesian democracy, Decentralization, Regional autonomy, Local governance, Identity politics Penelitian ini berpusat pada dampak desentralisasi terhadap demokrasi di Indonesia, terutama pada era pasca-Suharto, ketika penerapan pemerintahan terpusat selama puluhan tahun beralih ke desentralisasi. Mengacu pada Hofman & Kaiser (2006), kerangka teoretis menghubungkan antara desentralisasi dan demokrasi dengan menekankan pada partisipasi politik, pemberdayaan tata kelola regional, dan akuntabilitas. Desentralisasi tidak hanya dipandang sebagai sebuah mekanisme yang memberi masyarakat di tingkat akar rumput kapasitas pengambilan keputusan politik dan administrasi, tetapi juga memastikan bahwa pemerintah daerah tidak lagi bertanggung jawab langsung kepada pemerintah pusat di Jakarta – melainkan bertanggung jawab kepada konstituen lokal mereka. Namun, desentralisasi juga menghadirkan tantangan, terutama dalam masyarakat yang majemuk seperti Indonesia, dengan pengelolaan keragaman etnis dan agama menjadi isu yang signifikan. Meskipun desentralisasi dianggap sebagai wujud dari demokrasi Indonesia, berbagai masalah telah menghambat upaya untuk meningkatkan kualitas pemerintahan dan demokrasi lokal. Pada akhirnya, desentralisasi dan demokrasi saling bergantung erat, dengan kualitas salah satunya akan mencerminkan kualitas yang lain. Kata-kata Kunci: Demokrasi Indonesia, Desentralisasi, Otonomi daerah, Pemerintahan daerah, Politik identitas